2023
DOI: 10.1128/msphere.00454-23
|View full text |Cite
|
Sign up to set email alerts
|

In-depth biological characterization of two black soldier fly anti- Pseudomonas peptides reveals LPS-binding and immunomodulating effects

Laurence Van Moll,
Milan Wouters,
Jeroen De Smet
et al.

Abstract: As effector molecules of the innate immune system, antimicrobial peptides (AMPs) have gathered substantial interest as a potential future generation of antibiotics. Here, we demonstrate the anti- Pseudomonas activity and lipopolysaccharide (LPS)-binding ability of HC1 and HC10, two cecropin peptides from the black soldier fly ( Hermetia Illucens ). Both peptides are active against a wide range of Pseudomonas aeruginosa strains, including d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…The dietary supplementation of 5%, 10%, and 15% BSFPs could significantly reduce the concentration of IL-8 in the plasma of dogs. Research have shown that the anti-inflammatory activity of BSFL oil alleviated dextran sulfate sodium (DSS)-induced colitis by modulating Toll-like receptor (TLR) signaling [ 50 ], and the antimicrobial peptides (AMPs) from BSFL reduced LPS-induced nitric oxide and cytokine production in murine macrophage cells [ 51 ]. Furthermore, protein hydrolysate from black soldier fly larvae (BSFP), like other enzymatically hydrolyzed proteins from edible insects, might have anti-inflammatory capacity [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dietary supplementation of 5%, 10%, and 15% BSFPs could significantly reduce the concentration of IL-8 in the plasma of dogs. Research have shown that the anti-inflammatory activity of BSFL oil alleviated dextran sulfate sodium (DSS)-induced colitis by modulating Toll-like receptor (TLR) signaling [ 50 ], and the antimicrobial peptides (AMPs) from BSFL reduced LPS-induced nitric oxide and cytokine production in murine macrophage cells [ 51 ]. Furthermore, protein hydrolysate from black soldier fly larvae (BSFP), like other enzymatically hydrolyzed proteins from edible insects, might have anti-inflammatory capacity [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adding 15% lyophilized microalgae powder from schizochytrium in the diet can maintain a normal physiological state of the intestine by downregulating the gene expression level of pro-inflammatory cytokines (IL-6, IL-8, and IL-1β) in zebrafish [ 60 ]. A similar effect exists in black soldier fly larvae as black soldier fly larvae played an anti-inflammatory function by downregulating the IL-8 and IL-1β gene expressions and mediating the mechanism of toll-like receptors (TLR) signaling [ 61 ], and the antimicrobial peptides (AMPs) from black soldier fly larvae reduced the LPS-induced nitric oxide and cytokine production in murine macrophage cells [ 62 ]. Additionally, the protein hydrolysate from black soldier fly larvae also may have anti-inflammatory activity, as other enzymatically hydrolyzed proteins of edible insects [ 8 ].…”
Section: Discussionmentioning
confidence: 99%